RAHASIA AYAT-AYAT AMTS?L TENTANG KEHIDUPAN DUNIA DALAM AL-QUR’AN - Abdul Rasyid Ridho (el-'Umdah, 2018)
The main problem in this study is the existence of the verses Amtsâ l in the Qur’an especially those relating to the description of world life and its interpretation of several interpreters as an approach, as well as a description of human attitudes in addressing the life of the world. So that Amtsâ l as one of the sciences of the Qur’an as well as the method of the Qur’an in conveying messages, lessons, and wisdom and intent content in it. So on this basis, Amtsâ l isexpected to be able to provide an innovation as well as a method in a mental revolution towards the morals of both believers, infdels, and hypocrites, to be more aware of the beauty and pleasure of the world like a patamorgana that makes humans fall into the valley of destruction. Then the Qur’an as a guide for humans to get the salvation of the world and the hereafter